Effect of poly(ethylene glycol)-polyhedral oligomeric silsesquioxanes on the thermal and mechanical properties of biodegradable poly(l-lactide). (March 2017) - Tang, Lu; Qiu, Zhaobin
Abstract: In this work, a poly(l -lactide) (PLLA)/poly(ethylene glycol)-polyhedral oligomeric silsesquioxanes (PEG-POSS) nanocomposite was first prepared; moreover, the nonisothermal crystallization behavior, thermal stability, and mechanical properties of the nanocomposite were extensively studied and compared with those of neat PLLA. PEG-POSS was miscible with PLLA, as proved by a single glass transition temperature. As PEG-POSS increased the chain mobility of PLLA as a plasticizer, the nonisothermal cold and melt crystallization behaviors of PLLA were enhanced by PEG-POSS in the nanocomposite; furthermore, the thermal stability of PLLA was not obviously affected by PEG-POSS. In addition, PEG-POSS increased the ductility of PLLA as an efficient plasticizer and still maintained high Young's modulus. Highlights: A poly(l -lactide) (PLLA)/poly(ethylene glycol)-polyhedral oligomeric silsesquioxanes (PEG-POSS) nanocomposite was successfully prepared. PEG-POSS enhanced the nonisothermal cold and melt crystallization processes of the nanocomposite. PEG-POSS increased the ductility of PLLA as an efficient plasticizer.